Multilingual Information Access in South Asian Languages Second International Workshop, FIRE 2010, Gandhinagar, India, February 19-21, 2010 and Third International Workshop, FIRE 2011, Bombay, India, December 2-4, 2011, Revised Selected Papers - Majumder, Prasenjit; Mitra, Mandar; Bhattacharyya, Pushpak; Subramaniam, L. Venkata; Contractor, Danish; Rosso, Paolo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-proceedings of the Second and Third Workshops of the Forum for Information Retrieval Evaluation, FIRE 2010 and 2011, on Multi-lingual Information Access in South Asian Languages held in Gandhinagar, India, in February 2010 and in Bombay, India, in December 2011. The volume brings together revised and expanded versions of a total of 29 papers. The papers are organized in topical sections on various aspects of multi-lingual information access.
Query expansion based on equi-width and equi-frequency partition -- Ad-hoc retrieval with Marathi language -- Frequent case generation in ad-hoc retrieval of three Indian languages Bengali, Gujarati and Marathi.
Keywords: Computer science; Information storage and retrieval systems; Artificial intelligence; Text processing (Computer science; South Asian Languages; Computer Science; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Document Preparation and Text Processing; Asian Languages